KOMPOSISI DEWAN, KEPEMILIKAN INSTITUSIONAL DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Gabrielle Dika Duryat; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
The aim of this study is to examine the composition of the board and institutional ownership on disclosure of corporate social responsibility. This study uses capital structure and firm size as a control variable.The population in this study consists of manufacturing companies in Indonesia Stock Exchange for the period 2015 - 2017. Sample determined with purposive sampling method. Total sample of this research is 210 companies.This study used multiple regression analysis for hypotheses testing. The results of this study show that board size and institusional ownership has positive effect and significant on corporate social responsibility disclosure. This study also show that independence board commissioner has negative effect and significant on corporate social responsibility disclosure. Meanwhile, board education has no effect on corporate social responsibility disclosure.